2022
DOI: 10.3390/v14081684
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards the Development of a Universal Influenza Vaccine

Abstract: Influenza viruses are responsible for millions of cases globally and significantly threaten public health. Since pandemic and zoonotic influenza viruses have emerged in the last 20 years and some of the viruses have resulted in high mortality in humans, a universal influenza vaccine is needed to provide comprehensive protection against a wide range of influenza viruses. Current seasonal influenza vaccines provide strain-specific protection and are less effective against mismatched strains. The rapid antigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 182 publications
0
22
0
1
Order By: Relevance
“…Therefore, unlike the inactivated PR8 (H1N1) group, two immunizations with M2e SApNP followed by an H1N1 challenge may have enhanced the protection against a heterosubtypic H3N2 challenge. Overall, our results suggest that the adjuvanted M2ex3 I3-01v9a SApNP can be developed into an effective, pan-influenza A vaccine that may overcome the limitations of currently marketed influenza vaccines, including the lack of protection against antigenically drifted seasonal or novel pandemic strains . Furthermore, we also assessed our lead vaccine candidate, M2ex3 I3-01v9a SApNP, in a single low-dose formulation with potent adjuvants.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, unlike the inactivated PR8 (H1N1) group, two immunizations with M2e SApNP followed by an H1N1 challenge may have enhanced the protection against a heterosubtypic H3N2 challenge. Overall, our results suggest that the adjuvanted M2ex3 I3-01v9a SApNP can be developed into an effective, pan-influenza A vaccine that may overcome the limitations of currently marketed influenza vaccines, including the lack of protection against antigenically drifted seasonal or novel pandemic strains . Furthermore, we also assessed our lead vaccine candidate, M2ex3 I3-01v9a SApNP, in a single low-dose formulation with potent adjuvants.…”
Section: Discussionmentioning
confidence: 90%
“…Overall, our results suggest that the adjuvanted M2ex3 I3-01v9a SApNP can be developed into an effective, pan-influenza A vaccine that may overcome the limitations of currently marketed influenza vaccines, including the lack of protection against antigenically drifted seasonal or novel pandemic strains. 111 Furthermore, we also assessed our lead vaccine candidate, M2ex3 I3-01v9a SApNP, in a single low-dose formulation with potent adjuvants. Both CpG and MIW815 103 were found to significantly improve protection from lethal influenza A challenge compared to a conventional adjuvant, AP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, unlike the inactivated PR8 (H1N1) group, immunizations with M2e SApNP followed by an H1N1 challenge may enhance protection against heterosubtypic H3N2, addressing a major limitation of seasonal inactivated vaccines, which offer mostly strain-specific protection. Overall, our results suggest that the adjuvanted M2ex3 I3-01v9a SApNP can be developed into an effective, cross-protective influenza vaccine that may overcome the limitations of currently marketed influenza vaccines, including the lack of protection against antigenically drifted seasonal or novel pandemic strains (111). Furthermore, we also assessed our lead vaccine candidate, M2ex3 I3-01v9a SApNP, in a single, low-dose formulation with potent adjuvants.…”
Section: An M2e Vaccine Capable Of Eliciting Durable Antibody Respons...mentioning
confidence: 91%
“…Additionally, a recent study has reported that computationally engineered recombinant NA proteins containing consensus sequences show broad protection within the H1N1 subtype in mice [ 91 ]. Nucleic acid-based vaccines are also a potential strategy for an influenza vaccine [ 92 ]. This method depends on expressing the target antigen in vivo following vaccination with a plasmid encoding for the gene of interest [ 93 ].…”
Section: Na Universal Vaccinementioning
confidence: 99%